القياس عند المعتزلة دراسة وتقويما - Abdul Wahab Ahmad Khalil (Institut Agama Islam Negeri (IAIN) Kediri, 2018)
Mu’tazilah is a group of Islamic sects, who disagreed with the Muslims’ opinion on the issue of the great perpetrator, led by Wasel bin Atta and Amr ibn Ubaid, the time of the great Tabi’i, al-Hasan al-Basri. The Mu’tazilah built their doctrine on the five principles of monotheism: Tawheed, justice, promise and preaching, ordering virtue and forbidding evil. These five principles affect their ushul fiqh views, especially regarding qiyas. The aim of this research is to present the views of the Mu’tazilah regarding qiyas, as well as to explain their evidence and the opinions of their dissenters from the majority of scholars, and to express a strong opinion. The method used in this research is a descriptive, analytical, and critical method, where the researcher describes the views of the Mu’tazilah in relation with the qiyas as well as their evidences, and then analyzes and compares them with the views of their opponents from the majority of scholars, and then shows the strongest opinion between them. The research finds that the Nadzzam of the Mu’tazilah denied the authority of qiyas, and that Abu Hashim of the Mu’tazilah denied the analogy to an asset that did not stipulate his rule, while the Mu’tazilah generally saw that the illah can influent by itself. These three opinions are contrary to what the majority of scholars. After research and comparison, the researcher found that the views of the majority of scholars are stronger because their evidences are strong meanwhile the Mu’tazilah evidences are weak.